Pricing with confidence : 10 ways to stop leaving money on the table - Holden, Reed K.; Burton, Mark R., 1965- (Hoboken, NJ : Wiley, 2008)
Bad pricing is a great way to destroy your company's value, revenue, and profits. With ten simple rules, this book shows you how to deliver both healthy profit margins and robust revenue growth while kicking the dreaded discounting habit. The author.
PRICING WITH CONFIDENCE: 10 WAYS TO STOP LEAVING MONEY ON THE TABLE; CONTENTS; ACKNOWLEDGMENTS; INTRODUCTION: WHY PRICING IS SO HARD AND WHY MOST COMPANIES MESS IT UP; Rule One: Replace the Discounting Habit with a Little Arrogance; Rule Two: Understand the Value You Offer to Your Customer; Rule Three: Apply One of Three Simple Pricing Strategies; Rule Four: Play Better Poker with Customers; Rule Five: Price to Increase Profits; Rule Six: Add New Products and Services that Give You Negotiating Flexibility and Growth; Rule Seven: Force Your Competitor to React to Your Pricing.
Includes bibliographical references and index.
Print version record.
English.
John Wiley and Sons
Keywords: Pricing; Service industries -- Prices; Prix -- Fixation; Services (Industrie) -- Prix; BUSINESS & ECONOMICS -- Sales & Selling -- Management; Pricing; Service industries -- Prices